Curriculum policies for basic education and the education of portuguese language teachers: an integrative approach (Olhar de Professor, 2023)
Our objective in this text is to analyze, descriptively and normatively, the curricular integration project between BNCC and BNC-Formação regarding the Portuguese Language discipline, highlighting the importance of the university's involvement in the planning, implementation and evaluation of educational policies.  The analysis methodology is inspired by Dunn's (2018) integrative proposal, according to which policy analysis is done through the articulation of different disciplines and methods that allow explaining the processes of prescribing, forecasting, monitoring and evaluating policies. The analyzes showed that the current curricular guidelines do not annul university autonomy in the elaboration of course projects but establish new parameters for the exercise of this autonomy, aiming at the elaboration of curricula effectively committed to public interests.
Keywords: Policy analysis. Education of portuguese language teachers. Curriculum policies.